Comparing the Neural Correlates of Conscious and Unconscious Conflict Control in a Masked Stroop Priming Task - Jiang, Jun; Bailey, Kira; Xiang, Ling; Zhang, Li; Zhang, Qinglin (Frontiers in Human Neuroscience, 2016)
Although previous studies have suggested that conflict control can occur in the absence of consciousness, the brain mechanisms underlying unconscious and conscious conflict control remain unclear. The current study used a rapid event-related functional magnetic resonance imaging design to collect data from 24 participants while they performed a masked Stroop priming task under both conscious and unconscious conditions. The results revealed that the fronto-parietal conflict network, including medial frontal cortex (MFC), left and right dorsal lateral prefrontal cortex (DLPFC), and posterior parietal cortex (PPC), was activated by both conscious and unconscious Stroop priming, even though in MFC and left DLPFC the activations elicited by unconscious Stroop priming were smaller than conscious Stroop priming. The findings provide evidence for the existence of quantitative differences between the neural substrates of conscious and unconscious conflict control.